Affixation Process of Verbs in English and Bajo Language: A Contrastive Analysis - Sutriani, *Sutriani; Nasa, Rikardus; Darmawan, Darmawan (Riwayat: Educational Journal of History and Humanities, 2022)
This research was aimed at finding and describing about the affixation process of Verbs in Bajo Language, and the finding similarities and differences of verbs in English and Bajo language. This research was classified as a descriptive qualitative study. The techniques of data collection used in this research were interview and study document. The data were analyzed by using contrastive analysis. The result of the research showed that most of verbs in Bajo language changed based on meaning. The change on meaning could be formed from affixation process. Affixation process of verbs in Bajo language there is prefix process, suffix process, simulfix process, and confix process. While affixation process of verbs in English, there is prefix process, suffix process and confix process. The similarities of affixation process of verbs in English and Bajo language are both have the prefix process, suffix process, confix process in the morphological process. Difference was affixation process of verbs is in English did not have simulfix process of affixation process.